The role of University governance in ensuring the quality of ‎higher education sector: The case of Algeria‎‏ -‏ - bachir abdelali (Dirassat Journal Economic Issue, 2017)
This study aims to identify the most important principles of corporate governance, which imposed itself on enterprises with its multiple systems and different activities, which are considered an integrated system's oversight on how the performance of enterprises to clarify the relationship between the different actors and rules which must state on the basis of the enterprise in order to ensure a provided quality of services.The paper also discussed the application of this governance in universities and Algeria's experience in this area in order to ensure the quality of higher education.